Solving the problem of post-operative airway obstruction in Nasal/Sinus Surgery - Robert Kotler; Keith Wahl; Kimberly J Lee (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Sinus surgery, septoplasty-with or without turbinate reduction-and rhinoplasty are among the most common surgical procedures performed by our specialty. In 2006, 600,000 sinus surgeries were performed in the United States [1]. A recent paper reported more than 300,000 rhinoplasties done per year [1,2]. Septoplasties and ancillary procedures accounted for an additional 489,000 procedures [1].